2023
DOI: 10.1021/jacs.2c10655
|View full text |Cite
|
Sign up to set email alerts
|

Ligand-Directed Photocatalysts and Far-Red Light Enable Catalytic Bioorthogonal Uncaging inside Live Cells

Abstract: Described are ligand-directed catalysts for live-cell, photocatalytic activation of bioorthogonal chemistry. Catalytic groups are localized via a tethered ligand either to DNA or to tubulin, and red light (660 nm) photocatalysis is used to initiate a cascade of DHTz oxidation, intramolecular Diels−Alder reaction, and elimination to release phenolic compounds. Silarhodamine (SiR) dyes, more conventionally used as biological fluorophores, serve as photocatalysts that have high cytocompatibility and produce minim… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(12 citation statements)
references
References 97 publications
(134 reference statements)
0
7
0
Order By: Relevance
“…It was confirmed that the oxidation did not involve the generation of cytotoxic singlet oxygen or superoxide . Recently, this system was adapted to develop a photoinitiated intramolecular click-and-release system for organelle-targeted drug activation . Specifically, a dihydrotetrazine molecule 144 was designed, which by itself cannot be oxidized to the tetrazine in the biological system.…”
Section: Bioorthogonal Prodrugs Based On a Photoclick And Release Str...mentioning
confidence: 97%
See 1 more Smart Citation
“…It was confirmed that the oxidation did not involve the generation of cytotoxic singlet oxygen or superoxide . Recently, this system was adapted to develop a photoinitiated intramolecular click-and-release system for organelle-targeted drug activation . Specifically, a dihydrotetrazine molecule 144 was designed, which by itself cannot be oxidized to the tetrazine in the biological system.…”
Section: Bioorthogonal Prodrugs Based On a Photoclick And Release Str...mentioning
confidence: 97%
“…132 Recently, this system was adapted to develop a photoinitiated intramolecular click-and-release system for organelle-targeted drug activation. 133 Specifically, a dihydrotetrazine molecule 144 was designed, which by itself cannot be oxidized to the tetrazine in the biological system. In the presence of a SiR-based photocatalyst, 144 can be efficiently oxidized into tetrazine by using 660 nm light.…”
Section: Bioorthogonal Prodrugs Based On a Photoclick And Release Str...mentioning
confidence: 99%
“…Notably, in addition to drug release, light-induced functional molecule synthesis ( e.g. , tetrazines 92,93 ) and light-induced photocatalytic reactions for proximity labeling 94,95 are also important applications of photochemistry. However, providing exhaustive coverage of this subject matter exceeds the scope of this review.…”
Section: Physical Stimuli-induced Chemistry For Prodrug Activationmentioning
confidence: 99%
“…Additionally, a class of upconversion nanoparticles (UCNPs), designed to be excited by NIR light and emit visible or UV light, has been employed for controlled drug molecule release or single oxygen production as well. 90,91 Notably, in addition to drug release, light-induced functional molecule synthesis (e.g., tetrazines 92,93 ) and lightinduced photocatalytic reactions for proximity labeling 94,95 are also important applications of photochemistry. However, providing exhaustive coverage of this subject matter exceeds the scope of this review.…”
Section: Nir Light-induced Cleavage Chemistrymentioning
confidence: 99%
“…The unique nature of this natural enzyme has inspired numerous researchers to develop highly efficient and specific artificial catalysts through synthetic chemistry. 14–19…”
Section: Introductionmentioning
confidence: 99%